The growth of the small and medium-sized enterprises in the Polish economy and their influence on the labour market - Kwiatkowska, Walentyna (Comparative Economic Research. Central and Eastern Europe, 2010)
The small and medium-sized enterprises and self-employment significantly contribute to pro-employment growth in the economy. The main aim of the paper is to describe the determinants of development of SME sector in Poland and to show its significance as a generator of jobs. The article has been structure as follows. Section 2 provides the characteristics and importance of the small and medium-sized enterprises. Section 3 outlines the main provisions of the European Charter for Small Enterprises. Section 4 presents data illustrating SMEs’ growth trends and significance in Poland in the years 2003-2007 by the type of an enterprise, employment, and the share in GDP, foreign trade and investment. Section 5 discusses government’s policies towards utilising the sector’s growth potential for Poland. Section 6 presents major conclusions derived from the earlier discussion.